2009
DOI: 10.1073/pnas.0901695106
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic behavior of the major multidrug efflux pump AcrB of Escherichia coli

Abstract: Multidrug efflux transporters, especially those that belong to the resistance-nodulation-division (RND) family, often show very broad substrate specificity and play a major role both in the intrinsic antibiotic resistance and, with increased levels of expression, in the elevated resistance of Gram-negative bacteria. However, it has not been possible to determine the kinetic behavior of these important pumps so far. This is partly because these pumps form a tripartite complex traversing both the cytoplasmic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
186
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(202 citation statements)
references
References 40 publications
13
186
0
Order By: Relevance
“…S2C). Finally, all binding poses for cefazolin, for which we could not find any evidence for AcrB-mediated efflux in our quantitative efflux assay (28), were outside the binding pocket (Fig. S2C), confirming that prediction of binding at these locations has no functional significance.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…S2C). Finally, all binding poses for cefazolin, for which we could not find any evidence for AcrB-mediated efflux in our quantitative efflux assay (28), were outside the binding pocket (Fig. S2C), confirming that prediction of binding at these locations has no functional significance.…”
Section: Resultssupporting
confidence: 53%
“…We therefore examined the possible competition between the substrates by measuring the efflux of nitrocefin (a groove-binder; Fig. 3) quantitatively (28) in the presence and absence of potential competitors. Because the assay depends on the β-lactamase-catalyzed hydrolysis of nitrocefin, we could not use β-lactams as competitors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent paper presented differences in the affinity constant for some antibiotics [13]. Consequently, as the concentration of a determined compound is increased, competition for these internal binding sites favours the compound depending on the respective affinity constant ratio, thereby promoting intrabacterial retention of the antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…This can explain the divergence observed in the competitive capacity of the compounds with drugs of different classes (chloramphenicol, quinolones, ethidium bromide) for binding sites within the pump type (AcrB, MexB) as well as the level of expressed efflux pump activity in the tested strains. Kinetic studies have reported variation in the affinity constant of various -lactams for AcrB in E. coli cells [13]. This flexibility of the substrate site may be directly involved in the polyselectivity of the efflux pump; a site that can be modified by site-directed mutagenesis [15,16].…”
Section: Discussionmentioning
confidence: 99%